Family support after a family member’s suicide: A qualitative exploration - Franziska Marek; Nathalie Oexle (PLoS ONE, 2025)
Suicide bereavement presents unique challenges that shape how grief is experienced and supported within relational networks. Although family members often serve as a primary source of support, the interpersonal dynamics underlying such support remain understudied. This study explores how individuals bereaved by a family member’s suicide experience social support within the shared grief context of the family. Fifteen adults participated in semi-structured interviews conducted as part of a mixed-methods project in Germany, examining experiences and determinants of social support following suicide loss. Data were analyzed using qualitative content analysis, combining inductive and deductive coding. Two overarching themes were identified: (1) Contextual factors of family support , including grief reactions and coping patterns, shifts in family dynamics, and the distribution of support roles; and (2) Characteristics of family support , encompassing both supportive experiences—such as emotional closeness, open communication, and shared sense-making—and insufficient support—such as marginalization of grief and emotional neglect, often linked to pre-existing family strain. The availability and quality of support were influenced by protective buffering, relational withdrawal, discomfort surrounding suicide disclosure, and the reconfiguration of relationships after the loss. Extended family members played a significant role in assisting with childcare and relieving emotional burdens on grieving parents, although their support varied depending on attitudes toward suicide and levels of proactive engagement. Family support in suicide bereavement emerged as a dynamic process shaped by personal, relational, and sociocultural influences. These findings highlight the need for multilevel, integrative theoretical frameworks to capture the complexity of family support after suicide. This study underscores the value of systemic postvention strategies that foster emotional expression, shared sense-making, and stigma reduction, while recognizing that family may not be an accessible or supportive resource for all bereaved individuals.